Adjuntive nicergoline therapy for severe persistent corneal epithelial defects. - Valeria Oliva-Biénzobas; Enrique O. Graue-Hernandez; Guillermo Raul Vera-Duarte; Jesus Cabral-Macías; Juan Serna-Ojeda; Victor Boullosa; Arturo Ramirez-Miranda; Vishal Jhanji; Victor L. Perez; Alejandro Navas (AJO International)
Purpose: The aim of this study was to determine the effect of nicergoline in patients with persistent corneal epithelial defects. Methods: This is a prospective, non-comparative interventional study. The study included ten eyes of 9 patients with persistent corneal epithelial defects unresponsive to conventional therapy. Patients were treated with 10 mg nicergoline orally twice daily for at least two weeks. Slit-lamp examination, photography, corneal fluorescein dye testing, and best-corrected visual acuity were performed before and after treatment. Results: Two male and seven female patients with persistent corneal epithelial defects unresponsive to conventional therapy treated with oral nicergoline were included. The average age was 60.9 years (51–76 years). The most frequent diagnoses associated with persistent corneal defects were neurotrophic (3 patients) and exposure ulcer (2 patients). In eight eyes (72.7 %), epithelial defects entirely healed between 10 and 28 days of treatment with nicergoline (mean resolution time 17 days). Epithelial defects persisted in 2 eyes (27.3 %). Conclusion: Nicergoline represents a potential therapeutic option in patients with abnormal corneal healing responses. Further studies and clinical trials must be conducted to prove safety and efficacy as a treatment for persistent corneal epithelium defects in humans.